Borders and Mobility in Turkey Governing Souls and States - Fine, Shoshana (Mobility & Politics, 2018)
In the last two decades, Turkey has witnessed a variety of bordering interventions rooted in its problematisation as variously "transit," "destination," "European," "Muslim" and "safe." This book brings into focus seemingly disparate actors involved in such interventions, from the EU and international organisations to missionaries, security professionals and migrants themselves. It exposes how these actors depend upon the intersecting rationalities of managerialism, securitisation, humanitarianism and orientalism to control, contain, process, save and soul-lift mobile populations.